1985
DOI: 10.3354/meps024155
|View full text |Cite
|
Sign up to set email alerts
|

Ecological observations on the gorgonian sea fan Eunicella cavolinii'in the Bay of Naples

Abstract: Sea fans Eunicella cavolinii (Gorgonacea) do not grow above 15 m water depth on a vertical wall off the island of Ischia, Italy. There is a 90" change in orientation from parallel to the sea surface above 20 m to perpendicular to the sea surface below that depth. The vertical component of wave motion seems to determine orientation above 20 m, whereas below 20 m sea fans orient, as they do normally, to the horizontal water current. Sea fans were evenly spaced at all depths studied and did not overlap or shade o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…; cf. Russo 1985). Thus it is possible that total gorgonian biomass may be higher in greater depths than at our study sites.…”
Section: Discussionmentioning
confidence: 66%
“…; cf. Russo 1985). Thus it is possible that total gorgonian biomass may be higher in greater depths than at our study sites.…”
Section: Discussionmentioning
confidence: 66%
“…It has been suggested that size limitation occurs due to water flow (Birkeland, 1974;Sebens, 1984). Because fan-shaped gorgonians are passive filter feeders, their morphology is obviously an example of a growth form allowing optimal contact between living colony tissues and water (Theodor & Denizot, 1965;Wainwright & Dillon, 1969;Riedl, 1971;Grigg, 1972;Russo, 1985;Mistri & Ceccherelli, 1993;Weinbauer & Velimirov, 1995). Sebens (1982Sebens ( , 1984 postulated an optimal size for passive suspension feeders based on the ratio between prey capture or energy intake and metabolic cost as a function of water flow.…”
Section: Discussionmentioning
confidence: 98%
“…Building and maintaining such a "tree" growth model would be expensive in terms of energy and information. Fan-shaped gorgonians are passive filter feeders, since they remove microzooplankton from water currents flowing orthogonally to their greatest cross-sectional area (REDL, 1971; GRIGG, 1972; Russo, 1985). The maintenance of an invariable, lower ramification complexity is likely to be an optimal choice in managing the relationship between water and living tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While the number of studies on the autoecology of the Mediterranean shallowwater gorgonians (Cnidaria: Octocorallia) has recently increased (WEINBERG, 1978(WEINBERG, ,1979(WEINBERG, ,1980RUSSO, 1985;GILI et al, 1987GILI et al, ,1989SANTANGELO et al, 1988;SANTANGELO & ABBIATI, 1989;ABBIATI et al, 1991), papers dealing with growth rates, growth patterns, and possible sources of mortality of these colonial organisms remain scarce. In fact, only two somewhat earlier papers (VELIMIROV, 1975;WEINBERG & WEINBERG, 1979) deal with the problem of growth in such modular organisms in the Mediterranean basin.…”
Section: Problemmentioning
confidence: 99%